2022
DOI: 10.1021/acs.accounts.2c00066
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Tethered Nanoparticles: From Surface Engineering to Directional Self-Assembly

Abstract: Conspectus Current interest in nanoparticle ensembles is motivated by their collective synergetic properties that are distinct from or better than those of individual nanoparticles and their bulk counterparts. These new advanced optical, electronic, magnetic, and catalytic properties can find applications in advanced nanomaterials and functional devices, if control is achieved over nanoparticle organization. Self-assembly offers a cost-efficient approach to produce ensembles of nanoparticles with well-defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Several excellent reviews have been published on the selfassembly of colloidal particles, covering topics such as the principles that govern self-assembly, [42][43][44] the types of colloidal particles that can self-assemble, [45][46][47] and the characterisation, properties and applications of the resultant self-assembled superstructures. [48][49][50] We encourage interested readers to consult these references.…”
Section: Introductionmentioning
confidence: 99%
“…Several excellent reviews have been published on the selfassembly of colloidal particles, covering topics such as the principles that govern self-assembly, [42][43][44] the types of colloidal particles that can self-assemble, [45][46][47] and the characterisation, properties and applications of the resultant self-assembled superstructures. [48][49][50] We encourage interested readers to consult these references.…”
Section: Introductionmentioning
confidence: 99%
“…Adding surface ligands to colloidal building blocks provides a meaningful postsynthetic way to design anisotropic metal NPs and potentially guide their self-assembly in a specific pathway. , A number of methods in the literature have been reported to introduce surface ligands on metal NPs with regioselectivity: e.g., surface facet recognition, templated surface grafting, , and phase segregation of mixed ligands . Together with anisotropic NP topologies, site-specific ligand grafting can provide, or sometimes amplify, the directional interparticle interactions to drive NP assembly in a desired manner. , For example, gold nanorods (AuNRs) are a classic type of anisotropic building blocks having distinct LSPR bands along their transverse and longitudinal directions. , Without regioselective ligand coverage, AuNRs can pack as clusters with a local preferential direction along their sides; , however, with site-specific modification with ligands, AuNRs can be organized in an end-to-end fashion that allows their longitudinal LSPR coupling. An early example from Kumacheva and co-workers demonstrated that thiol-terminated polystyrene (PS-SH) could preferentially bind with Au (111) facets located at the two ends in tetrahydrofuran (THF), because the grafting density of cetyltrimethylammonium bromide (CTAB) on convex (111) facets was considerably lower as compared to that on flat (110) and (100) facets as the sides of AuNRs.…”
Section: Introductionmentioning
confidence: 99%
“…These hybrid nanomaterials are usually with a soft/soft or hard/soft interface which demonstrates extraordinary properties especially in their assembled structures that are not seen in their bulk due to the confinement effect. Representative examples include, when grafted to a hard material, polymer grafted nanoparticle or spherical brushes, 14‐16 polymer grafted nanorods, 17,18 and polymer grafted nanopores 19,20 . One typical example is poly(ethylene oxide) (PEO) grafted to gold crystal used in biomedical engineering due to its superior biocompatible, optical and nontoxic properties 21,22 .…”
Section: Introductionmentioning
confidence: 99%